2013
DOI: 10.1111/jam.12276
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cry1Da production inBacillus thuringiensisby driving expression from the σE-dependent BtI promoter

Abstract: Aims To increase the Cry1Da production in Bacillus thuringiensis by enhancing BtI promoter activity and fusion with upstream sequence from cry1Ab. Methods and Results The effects of joining the upstream sequence of cry1Ab that contains E2 subunit pyruvate dehydrogenase (PDH) recognition site to the cry1Da promoter as well as the effects of substitution mutation of conserved sequences of its BtI promoter on cry1Da expression was monitored by constructing cry1Da promoter‐lacZ fusions. Changing the −35 region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Based on a study of 700 newly isolated strains of B. thuringiensis from Qatar, divided into 16 different groups depending on the crystals formed, Nair et al [ 22 ] concluded that the isolates producing bipyramidal and cuboidal crystals carry all the Lepidopteran and Coleopteran specific insecticidal protein-coding genes, and these crystals are formed from the most common Cry1A, Cry1Ia, Cry1B, Cry1D, and Cry2 proteins. This statement partially contradicts the observations of Wanapaisan et al [ 77 ], who demonstrated that Cry1Da forms spherical crystals. Rosas-García linked the presence of proteins of Cry1 and Cry2 classes with bipyramidal and square crystals [ 78 ].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Based on a study of 700 newly isolated strains of B. thuringiensis from Qatar, divided into 16 different groups depending on the crystals formed, Nair et al [ 22 ] concluded that the isolates producing bipyramidal and cuboidal crystals carry all the Lepidopteran and Coleopteran specific insecticidal protein-coding genes, and these crystals are formed from the most common Cry1A, Cry1Ia, Cry1B, Cry1D, and Cry2 proteins. This statement partially contradicts the observations of Wanapaisan et al [ 77 ], who demonstrated that Cry1Da forms spherical crystals. Rosas-García linked the presence of proteins of Cry1 and Cry2 classes with bipyramidal and square crystals [ 78 ].…”
Section: Discussioncontrasting
confidence: 75%
“…The cubic crystals of B. thuringiensis strain BTG are most likely formed by Cry1Ab35 and Cry2Ab proteins, similar to the quasi-cuboidal shape of Cry1Ab21 crystal protein that was previously found in other Bt isolates [ 80 ]. The spherical crystals of BTG, however, are not due to the auto-crystallization of proteins of the Cry4 class (since the genome lacks the related genes), but to Cry1Da, as suggested by Wanapaisan et al [ 77 ].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, this bacterium can promote plant growth (Armada et al, 2018), bioremediate different heavy metals, biosynthesize metal nanoparticles (Jouzani et al, 2017), produce melanin (Cao et al, 2018), and even kill cancer cells (Moazamian et al, 2018). Due to its important value in agriculture, environment and medicine, mechanisms of ICPs formation and sporulation in B. thuringiensis have been extensively investigated at the transcriptional level (Park et al, 1998; Zhang et al, 1998, 1999; Aronson, 2002; Doruk et al, 2013; Wanapaisan et al, 2013; Hui et al, 2014), as has the study of its post-transcriptional, post-translational, and metabolic pathways (Yousten and Rogoff, 1969; Glatron and Rapoport, 1972; Baum and Malvar, 1995; Mathy et al, 2007; Wang et al, 2013a; Zheng et al, 2015). Heretofore, there are no reports to describe if and how HSPs affect accumulation of ICPs in B. thuringiensis .…”
Section: Introductionmentioning
confidence: 99%